Bioethical validation of the «human genome project» - Santos y Vargas, Leonides (Acta Bioethica, 2002)
This text proposes a number of reflections that issue fron the recent advancements that have taken place in investigations on the Human Genoma Project, which lead to the accelerated reinforcement of biomedical knowledge and technologies. The new statements upon human species' biological nature, legitimated by these new progress, allow us to reexamine the mythological and metaphysical explanations accumulated for millenia, facing a new philosophical anthropology. The advancements of medical science's interventions upon health and quality of life, allow us to evaluate again the legitimateness of a quantity of new biomedical possibilities. This text touches, too, in a particular way, the subject of cloning and it's different economic and political aspects.